Chitosan and Drying Temperature Optimization on the Quality of Bage Lemuru Fish using RSM Methods - Afgani, Chairul Anam; Mikhratunnisa; Hadi, Sofyan; Komarudin, Nurul Amri; Nuraisyah, Anni; Isworo, Rhestu (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2023)
Bage is a traditional fermented fish in Sumbawa made from lemuru fish (Sardinella lemuru). The aims of this study were to determine the chemical properties (moisture content and crude protein), microbial properties, and the panellist’s preferences for bage fish products after the addition of chitosan during the process. Optimization analysis using Response Surface Methodology showed that the temperature acquired was 60.93˚C. The chitosan concentration amounted to 3.51%, resulting in a water content of 23.47% and protein content of 49.91%. The number of microbial colonies in all treatments did not exceed the maximum limit of salted fish category product, based on SNI 8273 – 2016, but the fungal growth was found in samples with a temperature of 53 and 55˚C on the 20th day. The highest level of panellist preference for taste and aroma of bage fish was at a treatment temperature of 60 ° C with the addition of chitosan 4.62%, whereas the best texture was obtained by treatment at a temperature of 53˚C with the addition of 4.62% chitosan